Вибір хірургічного доступу у ході операцій на надниркових залозах - Ніконенко, О. С.; Завгородній, С. Н.; Губка, О. В.; Подлужний, О. О. (Clinical Endocrinology and Endocrine Surgery, 2008)
From 1987 to 2007 surgical treatment were performed in 50 patients with different adrenal tumors using thoracophrenolumbotomic (37,3%), lumbotomic (25,5%), laparotomic (7,8%) and videolaparoscopic (29,4%) approaches. The clinical characteristic of each approach was made. There are recommendations of their using depending on clinical situation. A videolaparoscopic adrenalectomy is recognized to be the most preferable, though the classical operations remain as an alternative to present day.